2017
DOI: 10.5206/cjsotl-rcacea.2017.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships in the Flipped Classroom

Abstract: This study examines the effectiveness of flipped classrooms in chemistry, and identifies relationships as a major factor impacting the success of flipped instruction methods. Examination of student interview data reveals factors that affect the development of peer-peer, peer-peer leader, and peer-expert relationships in first-year general chemistry and second-year organic chemistry flipped classrooms. Success was measured in terms of student perceptions of the effectiveness of the instruction, as well as stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 40 publications
0
27
0
13
Order By: Relevance
“…Phenomenography, a research framework that explores the outcome space of possible ways that a phenomenon can be experienced by participants, is appropriate for this type of study (Marton, 1981). Prior examples of our use of phenomenographic analysis in chemistry education can be found elsewhere McCollum et al, 2017;Skagen et al, 2018).…”
Section: Theoretical Framework and Analysis Methods: Phenomenography mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenomenography, a research framework that explores the outcome space of possible ways that a phenomenon can be experienced by participants, is appropriate for this type of study (Marton, 1981). Prior examples of our use of phenomenographic analysis in chemistry education can be found elsewhere McCollum et al, 2017;Skagen et al, 2018).…”
Section: Theoretical Framework and Analysis Methods: Phenomenography mentioning
confidence: 99%
“…Additionally, the disparate learning activities of their local classrooms shaped how team members experienced the collaborative learning, and hence influenced their reflections. Details on collaborative methods used in the Site 1 and Site 2 classrooms are reported elsewhere (McCollum, 2016;McCollum, Fleming, Plotnikoff & Skagen, 2017;Morsch, 2016;Skagen et al, 2018). In the collaborative learning experiences at Site 1 and Site 2, student partners were required to arrange a weekly time to video chat online in order to complete a collaborative assignment.…”
Section: Universities Involvedmentioning
confidence: 99%
“…By collecting data that represents the student voice, until saturation is achieved, we can generate the associated outcome space (Åkerlind, Bowden, & Green, 2005;Andretta, 2007;Booth, 1997). Examples of phenomenographic analysis in the Scholarship of Teaching and Learning (SoTL) / chemistry education research can be found elsewhere (McCollum, Sepulveda, & Moreno, 2016;McCollum, Fleming, Plotnikoff, & Skagen, 2017;Skagen et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Pre-lecture resources can reduce in-lecture cognitive load and diminish differences in achievement between students with prior knowledge of chemistry compared to students lacking this prior knowledge (Seery & Donnelly, 2012). Both classrooms in this study employed variations on flipped pedagogy as described elsewhere (McCollum, 2016;McCollum et al, 2017;Morsch, 2016;Morsch & Lewis, 2015).…”
Section: Course Designmentioning
confidence: 99%
See 1 more Smart Citation